2015
DOI: 10.3109/10641963.2015.1047938
|View full text |Cite
|
Sign up to set email alerts
|

Ideal cardiovascular health behaviors and factors prevent the development of hypertension in prehypertensive subjects

Abstract: Ideal cardiovascular health behaviors and factors are protective factors to prevent the progression from prehypertension to hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…has demonstrated that the cardiovascular health awareness program (CHAP) is associated with a reduction in systolic and diastolic blood pressure [ 19 ]. Our recent study also proves that ideal cardiovascular health behaviors and factors play a prevent role on the development of hypertension [ 20 ]. However, the knowledge about the impact and association of the dynamic changes of health metrics on the future development of new-onset hypertension are still limited currently.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…has demonstrated that the cardiovascular health awareness program (CHAP) is associated with a reduction in systolic and diastolic blood pressure [ 19 ]. Our recent study also proves that ideal cardiovascular health behaviors and factors play a prevent role on the development of hypertension [ 20 ]. However, the knowledge about the impact and association of the dynamic changes of health metrics on the future development of new-onset hypertension are still limited currently.…”
Section: Introductionmentioning
confidence: 62%
“…Being exhaustively studied, hypertension has been found highly prevalent in older age and male[ 27 32 ].Studies in recent years have also proved that people with a better baseline level of CHS have a strong and inverse association with risk of cardiovascular diseases and blood pressure level[ 3 , 20 , 33 ]. In our study, the change of cardiovascular health scores is significantly associated with the morbidity of new-onset hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Similar beneficial effects of achieving an above-average ideal CVH were also observed among participants in the REGARDS study [38]. Moreover, ideal CVH has been associated with various measures of subclinical CVD, including arterial stiffness, [3941] carotid atherosclerosis, [1416] and coronary artery calcium, [4244] as well as cardiovascular risk factors such as diabetes, [12] hypertension, [45] and depression [46]. While these results provide strong evidence for a protective effect of achieving ideal CVH on CVD and related conditions, previous investigations did not include American Indians, a minority group suffering from high rates of CVD, diabetes, and other risk factors.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have indicated the inverse association between the number of ICH metrics and the risks of hypertension 9,10 , type 2 diabetes mellitus 11,12 , CVDevents (stroke, heart failure, myocardial infarction, and fatal coronary disease) [13][14][15][16][17][18][19][20] , CVD mortality 21,22 , all-cause mortality 10,23 and concer 24,25 . However, most of the previous studies were conducted in western countries and Chinese urban areas [26][27][28] , much fewer in Chinese rural areas, which may not completely re ect the characteristics of Chinese rural population.…”
Section: Introductionmentioning
confidence: 99%